2016
DOI: 10.2147/cia.s125762
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcomes following reablement in community-dwelling older adults

Abstract: BackgroundReablement is a rehabilitation intervention for community-dwelling older adults, which has recently been implemented in several countries. Its purpose is to improve functional ability in daily occupations (everyday activities) perceived as important by the older person. Performance and satisfaction with performance in everyday life are the major outcomes of reablement. However, the evidence base concerning which factors predict better outcomes and who receives the greatest benefit in reablement is la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 29 publications
2
45
0
1
Order By: Relevance
“…Thus, contrary to policy ambitions of a universally applicable home care paradigm, reablement might instead be seen as an appropriate intervention only for the minority – in our study represented by Anna – who has a recent and sudden decline trajectory (Bødker , Rabiee and Glendinning , Tuntland et al . ). For the remaining majority of home care applicants, who are neither ‘recently independent’ nor only ‘temporarily dependent’, striving to become independent of care, however, might not be a meaningful pursuit.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, contrary to policy ambitions of a universally applicable home care paradigm, reablement might instead be seen as an appropriate intervention only for the minority – in our study represented by Anna – who has a recent and sudden decline trajectory (Bødker , Rabiee and Glendinning , Tuntland et al . ). For the remaining majority of home care applicants, who are neither ‘recently independent’ nor only ‘temporarily dependent’, striving to become independent of care, however, might not be a meaningful pursuit.…”
Section: Discussionmentioning
confidence: 97%
“…While no information on diagnosis was collected, it is reasonable to assume a similar mix and variety of diagnoses (e.g. orthopaedic, neurological, psychiatric) that has been presented in other trials conducted in a Nordic reablement context (Tuntland et al, ; Zingmark & Bernspång, ). Given that reablement is implemented for heterogeneous target groups, the focus and content of the intervention, and the role of different professionals may differ, for example, in relation to supporting clients after a hip fracture or clients diagnosed with neuropsychiatric limitations.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that in our study professionals consistently referred to compensatory care as a ‘previous’ practice, disregarding the fact that this form of care is still offered to those who are either unable or unwilling to engage in reablement or do not benefit from it. Thus, although previous studies have demonstrated that reablement is only likely to benefit a selected group of home‐care applicants recovering from, for instance, an illness or fracture (Rabiee & Glendinning, ; Tuntland et al, ), and that compensatory care, therefore, often exists alongside and in combination with reablement (Bødker, ; Bødker, Christensen, & Langstrup, ; Dahl et al, ), these two forms of care are far from being viewed as equal in a normative sense. Rather, they are placed in a normative hierarchy where compensatory care is considered an inferior form of care, and reablement a superior form.…”
Section: Discussionmentioning
confidence: 99%